The particle size distribution (PSD) as criteria for comparison of silver powders obtained by different methods of synthesis and by conditions of electrolysis - Avramović Lj.; Bugarin M.; Milanović D.; Conić V.; Pavlović M.M.; Vuković M.; Nikolić N.D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Silver powders produced by both electrochemical (galvanostatic (DC) and potentiostatic (POT) regimes of electrolysis) and chemical processes were examined by scanning electron microscope, and particle size distribution (PSD) of the obtained particles was done. In the DC regime, the current densities of –14.4 mA cm-2 for the nitrate (NIT; powder denoted with DC(NIT)) and –13.05 mA cm-2 for the ammonium (AM; DC(AM)) electrolytes were applied. In the POT regime, the used overpotentials were –90 mV (NIT(90)) and –150 mV (NIT(150)) for the nitrate, and –625 mV (AM(625)) and –925 mV (AM(925)) for the ammonium electrolytes. Reduction with hydrazine was used for chemical synthesis (powder denoted with HYD). On the basis of SEM and PSD analysis, Ag powders were grouped into three groups. In the first group DC(AM), AM(925) and HYD powders with the (8.4–8.9 %) volume ratios were placed. In the second group were AM(625) and DC(NIT) powders with the (6.5–6.6 %) volume ratios. NIT(90) and NIT(150) powders with the volume ratios of (5.2–5.7 %) made the third group. The obtained volume ratios were correlated with the morphology of synthesized particles in order to perceive advantages and lacks of powder production via electrochemical and chemical routes.